TMPRSS2-ERG fusion protein regulates insulin-like growth factor-1 receptor (IGF1R) gene expression in prostate cancer: involvement of transcription factor Sp1 - Sharon, Shilhav Meisel (Oncotarget, 2016)
Prostate cancer is a major health issue in the Western world. The most common gene rearrangement in prostate cancer is the TMPRSS2-ERG fusion, which results in aberrant expression of the transcription factor ERG. The insulin-like growth factor-1 receptor (IGF1R) plays a key role in cell growth and tumorigenesis, and is overexpressed in most malignancies, including prostate cancer. In this study we show that TMPRSS2-ERG mediates its tumorigenic effects through regulation of IGF1R gene expression. Silencing of T-ERG in VCaP cells resulted in downregulation of both IGF1R and Sp1, a critical IGF1R regulator. Co-immunoprecipitation assays revealed a physical interaction between transcription factors ERG and Sp1, with potential relevance in IGF1R gene regulation. In addition, transactivation of the IGF1R gene by ERG was mediated at the level of transcription, as indicated by results of promoter assays. To identify new co-activators of the TMPRSS2-ERG fusion protein we performed mass spectrometry-based proteomic analyses. Among other interactors, we identified AP-2 complex subunit mu (AP2M1) and caveolin-1 (CAV1) in association with ERG in cell nuclei. These proteins play a mechanistic role in IGF1R internalization. Our analyses are consistent with a potential novel function of TMPRSS2-ERG as a major regulator of IGF1R gene expression. Results may impinge upon ongoing efforts to target the IGF1R in the clinics.